Impressions of Luis de Molina about the trade of African slaves - Henrique Joner (Patristica et Mediævalia, 2015)
This article presents Luis de Molina’s observations on the black slave trade in the 16th century. Developing his legal and moral arguments about this growing market, Molina turns his attention to this business and seeks to listen to those who were directly or indirectly related to it. He also describes in detail the dreadful circumstances involved in the enslavement of Africans, denounces the authorities responsible for allowing such atrocities and demands their justification, and calls for a fast end to this unjust and perverse market. The intention of the article is to demonstrate the circumstances and authorities involved in this trade that supplied the New World with labor and guaranteed its economic development.